Validation and application of hair analysis for the detection of methamphetamine in young thai adults - Junkuy,A. (IOS Press, 2015)
© 2013 is published by the Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand. Background: To date, blood and urine analyses have been the major methods of detecting methamphetamine (MA) use in Thailand. Recently, hair analysis has been introduced as an alternative and complementary procedure. Asian Biomedicine Objectives: To validate a simple, rapid, and economical method of analyzing hair for MA and its metabolite, amphetamine (AM). Methods: The analysis employed solid-phase microextraction (SPME) coupled with gas chromatography and mass spectrometry (GC-MS). Simplicity, rapidity, and economy were achieved, in part, by optimizing SPME conditions and by eliminating deuterated reagents and the derivatization step in GC-MS. The validated method was employed to detect and quantify MA in 1,111 hair samples of young Thai research volunteers who reported using MA in the form of so-called "yaba" tablets at least 3 times during the previous 3 months. Results: Validated data from the study indicated that the method's linearity, accuracy, precision, limit of detection (LOD) and limit of quantitation (LOQ) met international standards for hair analysis of MA. Expressed as ng of MA per mg of hair (ng/mg), the LOQ was 0.5 ng/mg (102.39% accuracy, 5.46% precision). The method was less sensitive for quantification of AM in hair, with a LOQ of 2.5 ng/mg (103.41% accuracy, 6.95% precision). Using 0.5 ng/mg as a cutoff in the analysis of samples provided by admitted MA users, the study yielded an overall detection rate for MA of 35.5%, with a range of 0.51-54.61 ng/mg; the mean MA level was 4.90 6.78 (?SD) ng/mg. Thirty-one percent of the participants reported they had consumed fewer than 10 yaba tablets during the previous 3 months. Of this group, 29% had hair samples that tested positive for MA. Detection rates trended upwards with increased yaba use. No relationship was found between the number of yaba tablets reportedly consumed and the concentration of MA detected in hair. Conclusions: This study validated a rapid, simple, and economical SPME/GC-MS technique for quantification of MA in hair. The method was less sensitive for quantification of AM.